PENERAPAN METODE STATISTICAL PROCESS CONTROL (SPC) PADA PENGOLAHAN BIJI KAKAO - Ida Bagus Suryaningrat; Noer Novijianto; Nur Faidah (Faculty of Agricultural Technology, University of Jember, 2015)
Cocoa is the one of agricultural commodities with high contribution in national economy. Low quality and defeccted product during process were still problems faced by cocoa processing unit. The objectives of this research were to identify defeccted product during processing and to create alternatives ways to solve problems based on SPC. SPC (statistical process control) with p chart, pareto chart and fishbone chart were implemented in this reasearch to analyze data which collected from field. The results of this research found that all of processing unit in the plantation were still under control (inside control range). Over ripe (almost damage) was dominant damage product during harvesting process, and broken bean was dominant damage product during drying process. Man, method, raw material, machine (tools) and environment were important factors (cause factors) in of cocoa bean process. Proportion of worker number, improved skill and high intencity of controlling were still required to improve cocoa bean product.Keywords: Statistical Process Control (SPC), processing, cocoa beans